Socialization of the Use of Smart TVs as a Means of Improving Communication Quality and as a Learning Medium in Indonesia's 3T Regions: Pengabdian - Winda Fashihah; Kemmala Dewi; Wakhibah Dwi Khusnah; Ida Wahyu Wijayati; Aris Krisdiyanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The gap in access to information technology in Indonesia's Frontier, Outermost, and Disadvantaged (3T) regions remains a crucial challenge in efforts to equalize the quality of national education and communication. This community service article aims to document and analyze the effectiveness of socialization of the use of Smart TVs as a means of improving the quality of communication and learning media in 3T regions. The main problems identified are low digital literacy and the use of technological devices that are limited to conventional entertainment functions, despite the enormous potential of internet-based devices to reduce the distance of information. The community service implementation method is carried out through a Community Development approach that includes technical demonstrations, interactive workshops on the use of digital education features, and mentoring for teachers and parents in curating learning content. The results of the community service show an increase in community understanding of the transformative function of Smart TVs as a window to global information and a dynamic instructional tool in schools with limited human resources. This article concludes that strengthening digital literacy through devices familiar in the domestic environment such as television can be an effective bridge to digital inclusion for communities in remote areas.